Accumetrics-based clopidogrel dosing in endovascular neurosurgery. (November 2015) - Wong, Paul; Tesoro, Eljim; Aletich, Victor; Alaraj, Ali
Abstract : Introduction: The role of the VerifyNow test to guide clopidogrel therapy in neurosurgical patients is still unclear. This study compared outcomes in patients undergoing neurointerventional procedures on either standard clopidogrel or tailored clopidogrel regimens. Methods: Adult patients undergoing neurointerventional procedures from 1 May 2002 to 31 December 2012 at the University of Illinois Hospital and Health Sciences System were included if they were receiving dual antiplatelet therapy (DAPT) for their procedure. Patients were categorised based on the use of VerifyNow to guide therapy. The primary endpoint was the incidence of thromboembolic complications within 6 months post procedure. Secondary endpoints included the incidence of haemorrhagic complications and death. P2Y12 reaction units (PRU) were recorded when available and categorised based on relation to procedures and/or events. Results: A total of 228 patients were screened with 130 meeting inclusion criteria. Ninety patients were grouped into the standard therapy arm and 30 patients into the tailored therapy arm. There were no differences in the incidence of ischaemic complications (1.1 vs 2.5%, P  = 0.522), haemorrhagic complications (17.8 vs 15.0%, P  = 0.455) or death (3.0 vs 0%, P  = 0.552). Seventeen of 32 patients (53.1%) with PRUs were clopidogrel resistant defined as a PRU >180. Discussion: Use of the VerifyNow test to guide clopidogrel therapy in patients undergoing neurointerventional procedures did not result in a decrease in the incidence of thromboembolic complications compared to standard therapy. There was no difference in the incidence of haemorrhagic complications or death. Further studies are needed to evaluate the impact of tailored therapy using VerifyNow.